Flexible Temperature Sensors - Liu, Ruping; He, Liang; Cao, Meijuan; Sun, Zhicheng; Zhu, Ruiqi; Li, Ye (Frontiers in Chemistry, 2021)
Temperature reflects the balance between production and dissipate of heat. Flexible temperature sensors are primary sensors used for temperature monitoring. To obtain accurate and real-time information of temperature, various flexible temperature sensors are developed according to the principle of flexible resistance temperature detector (FRTC), flexible thermocouple, flexible thermistor and flexible thermochromic, showing great potential in energy conversion and storage. In order to obtain high integration and multifunction, various flexible temperature sensors are studied and optimized, including active-matrix flexible temperature sensor, self-powered flexible temperature sensor, self-healing flexible temperature sensor and self-cleaning flexible temperature sensor. This review focuses on the structure, material, fabrication and performance of flexible temperature sensors. Also, some typical applications of flexible temperature sensors are discussed and summarized.